Reversal deterioration of renal function accompanied with primary hypothyrodism - Dragović Tamara (Vojnosanitetski Pregled)
Introduction. Hypothyroidism is often accompanied with decline of kidney function, or inability to maintain electrolyte balance. These changes are usually overlooked in everyday practice. Early recognition of this association eliminates unnecessary diagnostic procedures that postpone the adequate treatment. Case report. Two patients with elevated serum creatinine levels due to primary autoimmune hypothyroidism, with complete recovery of creatinine clearance after thyroid hormone substitution therapy are presented. The first patient was a young male whose laboratory tests suggested acute renal failure, and the delicate clinical presentation of reduced thyroid function. The second patient was an elderly woman with a history of a long-term signs and symptoms attributed to ageing, including the deterioration of renal function, with consequently delayed diagnosis of hypothyroidism. Conclusion. Serum thyrotropin and thyroxin levels measurement should be done in all cases of renal failure with undefined renal desease, even if the typical clinical presentation of hypothyroidism is absent. Thyroid hormone assays sholud also be performed in all patients with chronic kidney disease whose kidney function is rapidly worsening.